A NOVEL APPROACH FOR CLUSTERING IN WIRELESS SENSOR NETWORKS BASED ON EN-ERGY EFFICIENT TREE BASED CLUSTERING:EETC - Dr. Ankur Goyal, Dr Akash Saxena, Atul kumar Srivastava, Shivam Mudgal (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Wireless sensors network as an energy consumption technique has been widely discussed in several studies. However, factors such as cluster formation or Cluster Head (CH) assignment node approach have a dramatic effect on network performance as reducing energy efficiency involves restricted resources or network data traffic. For this purpose, we have developed a new energy-efficient tree-based clustering (EETC) model which is the combination of two algorithms, K-Median and Bellman ford algorithms. In the first unit, a hierarchical protocol for routing based on the K-median algorithm transforms a space partition data frame into node organizer clusters. The key purpose of this approach is to reduce sensor node communication by using clustering techniques. In this paper, K-Median is used to measure a decent median among sensor nodes to obtain an optimal result of a cluster. The related cluster heads may then be selected. The balancing of network demands among clusters will increase energy efficiency or effectively prolong network life. Simulation findings show the efficiency in terms of energy consumption or cellular network life of our proposed algorithm over other popular protocols. Bellman-Ford algorithm is used later for establishing the communication among the CHs hence making a secure connection for nodes. The results are compared with the R-LEACH protocol in the MATLAB and parameters like nodes dead rounds, energy consumption has been calculated.